Kegiatan Seni Mewarnai Melalui Media Gambar pada Anak Usia Dini di RA AL HIKMAH Doroampel - Dita Hendriani; Dwi Junianto (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Coloring activities in early childhood as a basic foundation for improving fine motor skills. The purpose and objective of this coloring service is to stimulate the creativity of early childhood which has a positive effect as a vehicle for children's expression, color recognition, use of fingers, wrist skills and coordination between eyes and hands. The method approach used is through three stages, namely the preparation stage, the implementation stage and the evaluation stage of the activity. This service is located at the early childhood school RA AL HIKMAH Doroampel, Sumber Gempol, Tulungagung. The results of coloring activities in early childhood are obtained that students are able to express their art creations with various color combinations used, activities take place enthusiastically and conducively and improve fine motor skills of early childhood.